2012
DOI: 10.1007/s00216-012-6626-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of insulin-like growth factor-1 in dried blood spots for detection of growth hormone abuse in sport

Abstract: There is significant evidence that athletes are using recombinant human growth hormone (rhGH) to enhance performance, and its use is banned by the World Anti-Doping Agency and professional sports leagues. Insulin-like growth factor-1 (IGF-1) is the primary mediator of growth hormone action and is used as a biomarker for the detection of rhGH abuse. The current biomarker-based method requires collection and expedited shipment of venous blood which is costly and may decrease the number of tests performed. Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 24 publications
0
78
0
1
Order By: Relevance
“…For example, we were not able to detect tryptic peptides from insulin-like growth factor-1(P05019) in digested DBS samples. However, Cox and coworkers developed an elegant analytical method for this 7.6 kDa protein by using an acetonitrile precipitation step to remove most background proteins (29,30). In addition, detectability could be improved by using multidimensional separations or immunoaffinity enrichment prior to LC/MRM-MS (45)(46)(47).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we were not able to detect tryptic peptides from insulin-like growth factor-1(P05019) in digested DBS samples. However, Cox and coworkers developed an elegant analytical method for this 7.6 kDa protein by using an acetonitrile precipitation step to remove most background proteins (29,30). In addition, detectability could be improved by using multidimensional separations or immunoaffinity enrichment prior to LC/MRM-MS (45)(46)(47).…”
Section: Resultsmentioning
confidence: 99%
“…deWilde et al used LC/MRM-MS to quantify ceruloplasmin as a screen for Wilson's disease (28). Recently, Cox et al reported LC/ MRM-MS methods for quantifying insulin-like growth facter-1 for the detection of human growth hormone abuse in sports (29,30).…”
mentioning
confidence: 99%
“…Finally, novel, previously unknown macromolecules (i.e., TB500 17-23 fragment), with no current approval for human therapeutic use (i.e., agents under preclinical or clinical development, designer drugs, or compounds approved only for veterinary use), but illegally marketed (e.g., via Internet websites) [5] are included in section S0 ''Non-approved substances''. Different analytical approaches have already been developed and published to detect these compounds in nutritional supplements [6][7][8][9][10] and in doping control samples (either blood [11][12][13][14][15][16][17][18] or urine [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]), employing immunological [26,[35][36][37], electrophoretic [16][17][18][19]27], or liquid chromatography-mass spectrometry techniques [6-15, 20-25, 28-34] or a combination of different analytical technologies. In general, the most effective analytical approach (combined sample pretreatment and the instrumental method) has to take into ...…”
Section: Introductionmentioning
confidence: 99%
“…whole blood spotted on CMC. Both different temperatures [room temperature (RT), 8 and −25°C for 45 days] and storage lengths were tested (7,14, and 45 days for RT samples). All samples were kept in airtight zip-bags during the storage period.…”
Section: ■ Results and Discussionmentioning
confidence: 99%